Analysis of Efforts to Improve the Quality of Health in Kampung Sayang Ibu Anak through Exclusive Breastfeeding Ambassadors and Women's Reproductive Health in Kiarapedes Village, Purwakarta Regency, Indonesia - Arifianingsih, Ayu (HM Publisher, 2024)
Kampung Sayang Ibu Anak (KSIA) is a program that aims to improve the quality of maternal and child health. One of the efforts made in KSIA is through the role of ambassador for breastfeeding and women's reproductive health. This research aims to analyze efforts to improve the quality of KSIA health through breastfeeding and women's reproductive health ambassadors in Kiarapedes Village, Purwakarta Regency, Indonesia. This research uses a qualitative approach with a case study method. The data collection techniques used were in-depth interviews, observation and documentation. Data were analyzed using the Miles and Huberman model, namely data reduction, data presentation, and drawing conclusions. The research results show that efforts to improve the quality of KSIA health through breastfeeding and women's reproductive health ambassadors in Kiarapedes Village have gone well. Ambassadors for breastfeeding and women's reproductive health have played an active role in providing education, counseling and assistance to pregnant women, breastfeeding mothers and adolescent girls. The education and counseling provided by breastfeeding and women's reproductive health ambassadors has increased the knowledge and understanding of pregnant women, breastfeeding mothers and adolescent girls about exclusive breastfeeding and women's reproductive health. In addition, the assistance provided by breastfeeding and women's reproductive health ambassadors has increased the self-confidence and ability of pregnant women, breastfeeding mothers and adolescent girls to care for themselves and their families. In conclusion, efforts to improve the quality of KSIA health through breastfeeding and women's reproductive health ambassadors have had a positive impact on increasing knowledge, understanding, self-confidence and abilities of pregnant women, breastfeeding mothers and adolescent girls.